Native disorder mediates binding of dynein to NudE and dynactin. (19th September 2012) - Barbar, Elisar
Abstract : In the present paper, I report the molecular overlap of the linkage of three essential protein complexes that co-ordinate the formation of the mitotic spindle. These proteins are dynein, a large motor complex that moves machinery inside cells, and two of its regulators: a protein complex called dynactin, a dynein activator, and a protein called NudE whose depletion in mice produces a small brain and mental retardation. What is intriguing about the dynein–dynactin–NudE interplay is that dynactin and NudE bind to a common segment of dynein that is intrinsically disordered. Elucidating differences in their binding modes may explain how one regulator can be selected over the other even when both are present in the same cellular compartment. These results not only have a far-reaching impact on our understanding of processes essential for the formation and orientation of the spindle, but also offer a novel role for protein disorder in controlling cellular processes, and highlight the advantages of NMR spectroscopy in elucidating atomic-level characterization of extremely complex dynamic cellular assemblies.